COMMON CHRISTMAS SONGS OF HUNGARIANS AND ROMANIANS IN THE TRANSYLVANIAN PLAIN - GERGELY, Zoltán (Studia Universitatis Babes-Bolyai Musica, 2015)
Until the middle of the 20th century carolling was one of the most popular folk traditions in Hungarian speaking areas. In several Transylvanian and Moldavian communities this continued until the end of the 20th century. On the Transylvanian Plain this tradition still lives on today. Due to the interethnic relationship between the two communities, we can discover many Romanian melodies and texts in the repertoire of the Hungarians on the Transylvanian Plain. The purpose of the study is the presentation and analysis of these.